1999
DOI: 10.1002/masy.19991480107
|View full text |Cite
|
Sign up to set email alerts
|

Sequences distribution of poly(ethylene terephthalate‐isophthalate) copolymers: Experimental TREF study and numerical simulation

Abstract: The fractionation of a statistical copolyester made of poly(ethy1ene terephthalate-isophthalate) has been performed using Temperature Rising Elution Fractionation (TREF). TREF fractions were analyzed by size exclusion chromatography, thermal analysis, 'H-nuclear magnetic resonance and small angle X-Ray diffractometry. Results show that the fractions exhibit both interchain and intrachain defect distribution. As the intrachain defect distribution can not be determined by experimental techniques, a computer simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…A collection of chains with similar longest crystallisable sequences can still contain a broad intra-molecular distribution of crystallisable sequence lengths, which explains the presence of multiple melting peaks. In an analogous case, Lodefier et al [28,29] have shown that the TREF fractions of random copolyester have broad stepwise isothermal segregation technique melting curves, because of the broad intra-molecular distribution of crystallisable sequence lengths in the chains. The narrower peaks of the highermelting fractions indicate that these fractions contain more uniform material.…”
Section: Resultsmentioning
confidence: 96%
“…A collection of chains with similar longest crystallisable sequences can still contain a broad intra-molecular distribution of crystallisable sequence lengths, which explains the presence of multiple melting peaks. In an analogous case, Lodefier et al [28,29] have shown that the TREF fractions of random copolyester have broad stepwise isothermal segregation technique melting curves, because of the broad intra-molecular distribution of crystallisable sequence lengths in the chains. The narrower peaks of the highermelting fractions indicate that these fractions contain more uniform material.…”
Section: Resultsmentioning
confidence: 96%
“…The incorporation of the isophthalic units into PET causes a steady decrease in the T g of PET. [9][10][11][12][13][14][15] This trend is reversed, however, when the isophthalic units are replaced by t BI units. [16][17][18][19] The variation of the T g with the content of t BI unit along the five series (CHDM contents ¼ 0, 5, 10, 15, and 20%) is compared in Table I, revealing that a nearly linear trend is followed in every case.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Table I shows how T g varies as the content of CHDM increases (PET, PETG 5 , PETG 10 , PETG 15 , and PETG 20 ).…”
Section: Thermal Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…PET copolymers containing minor amounts of isophthalic acid as the second comonomer have been extensively investigated for their great industrial importance 5–10. In these copolymers, the sterical disturbance created by the 1,3‐phenylene units in the chain of PET is known to repress considerably the crystallization rate and to restrict the occurrence of crystallinity to compositions in isophthalic acid lower than 20 mol % 6, 7.…”
Section: Introductionmentioning
confidence: 99%